Household farm production diversity and micronutrient intake: Where are the linkages? Panel data evidence from Uganda - Sekabira, H.; Nalunga, S.; Umwungerimwiza, Y.D.; Nazziwa, L.; Ddungu, S.P. (MDPI, 2021)
Hunger and malnutrition are key global challenges whose understanding is instrumental to their elimination, thus realization of important sustainable development goals (SDGs). However, understanding linkages between farm production diversity (FPD) and household micronutrient intake is important in mapping micronutrient deficiencies and hidden hunger. Such understanding would inform appropriate interventions against malnutrition. Unfortunately, empirical literature is scarce to sufficiently inform such understanding. Using nationally representative panel survey data covering about 3300 households, we study linkages between FPD and nutrition, and associated impact pathways. We analyze data using panel regression models. Results show that at least half of sample was deficient in daily energy, iron, zinc, and vitamin A intake vis-à-vis FAO recommendations. Deficiencies were most severe (85%) with vitamin A. Positive and significant associations (about 1% for each added crop/livestock species) exist between FPD and daily household energy, iron, zinc, and vitamin A intake. FPD impacts energy and micronutrient intake via two main consumption pathways; markets (about 0.01% for each shilling), and own farm production (about 0.1% for each shilling). Therefore, own farm production yields better outcomes. Gender effects also exist. Male-headed households exhibited better nutrition outcomes (energy—11%, iron—8%, and zinc—12%) mostly via markets. Effects on Vitamin A were also positive although insignificant.